'Commoning' at the borderland: ecovillage development, socio-economic segregation and institutional mediation in southwestern Alentejo, Portugal - Esteves, A. M. (Journal of Political Ecology, 2017)
This article sheds light on the exclusionary dynamics that emerge when the construction of commons-based alternative political ecologies does not take political economy considerations into account. It analyses the relationship between Tamera – Healing Biotope I, and the ecosystem, population and institutions of the region of southwestern Alentejo, Portugal, where this ecovillage is located. Tamera is based on a prefigurative process of "commoning", transplanted from Central European counter-culture, which created a "borderland" that spatially segregates and at the same time creates a point of contact between two contrasting cultural, ecological and socio-economic realities. However, maintaining the "borderland" granted the community access to the resources needed to develop its vision, while countering existing regulations, although eventually involving the state in the development of a new regulatory framework. Since the mid-2000s, Tamera has been engaging in cultural dialogue with the local population, with the support of the municipality. The analysis raises the question of how to develop regulatory and financial instruments that support ecovillages in promoting inclusive strategies of economic sustainability, integrating them in placebased dynamics of regional development. The specificities of their biophysical and social processes must be taken into account, as well as their vocation as "testfields" for sustainability.